The Effect of Alkaline Cations on the Intercalation of Carbon Dioxide in Sepiolite Minerals: A Molecular Dynamics Investigation - Tavanti, Francesco; Muniz-Miranda, Francesco; Pedone, Alfonso (Frontiers in Materials, 2018)
The ability of the sepiolite mineral to intercalate CO2 molecules inside its channels in the presence of different alkaline cations (K+, Na+ and Li+) has been studied by classical Molecular Dynamics simulations. Starting from an alkaline-free sepiolite crystalline model we built three models with stoichiometry Mg320Si440Al40O1200(OH)160X+40•480H2O. On these models, we gradually replaced the water molecules present in the channels with carbon dioxide and determined the energy of this exchange reaction as well as the structural organization and dynamics of carbon dioxide in the channels. The adsorption energy shows that the Li-containing sepiolite mineral retains more carbon dioxide with respect to those with sodium and potassium cations in the channels. Moreover, the ordered patterns of CO2 molecules observed in the alkaline-free sepiolite mineral are in part destabilized by the presence of cations decreasing the adsorption capacity of this clay mineral.